2014
DOI: 10.3390/molecules190913374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Apitherapy Formulations against Carbon Tetrachloride-Induced Toxicity in Wistar Rats after Three Weeks of Treatment

Abstract: Abstract:The human body is exposed nowadays to increasing attacks by toxic compounds in polluted air, industrially processed foods, alcohol and drug consumption that increase liver toxicity, leading to more and more severe cases of hepatic disorders. The present paper aims to evaluate the influence of the apitherapy diet in Wistar rats with carbon tetrachloride-induced hepatotoxicity, by analyzing the biochemical determinations (enzymatic, lipid and protein profiles, coagulation parameters, minerals, blood cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
4
8
0
Order By: Relevance
“…Our observations add further evidence for the previous reports of [36] who reported that CCl4 increases lipid profile through cellular oxidative stress, one of the main causes of hepatic lesions produced by CCl4 mediated by the free radicals derived from this toxic substance. The intensification of the oxidative stress enhances the influence of non-essential fatty acids which, in turn, increase the serum and tissue levels of cholesterol and triglycerides.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our observations add further evidence for the previous reports of [36] who reported that CCl4 increases lipid profile through cellular oxidative stress, one of the main causes of hepatic lesions produced by CCl4 mediated by the free radicals derived from this toxic substance. The intensification of the oxidative stress enhances the influence of non-essential fatty acids which, in turn, increase the serum and tissue levels of cholesterol and triglycerides.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that antioxidants and flavonoids can act as inhibitors of lipid peroxidation by neutralising the radicals of polyunsaturated fatty acids and by interrupting the chain reactions, suppress the influence of non-essential fatty acids which, in turn, decrease the serum and tissue levels of cholesterol and triglycerides [36].…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with Andritoiu et al [55]. An improvement of the A/G ratio revealed in rats pretreated with C. comosum extract was due to an increase of serum albumin with a relative decrease of the globulin values.…”
Section: Discussionsupporting
confidence: 93%
“…Azima tetracantha leaves extract restored cholesterol to normal levels, like silymarin restoring TGS to normal levels (Table 1) Results of this investigation disclosed that CCl 4 increased serum levels of triglycerides, cholesterol, and LDL, while it produced a remarkable decrease in serum levels of HDL. Our observations add further evidence for the previous reports of ( Andritoiu et al, 2014), that CCl 4 aggravates lipid pro ile by cellular oxidative stress. Mediated by the free radicals derived from CCL 4, hepatic lesions are produced.…”
Section: Effect Of Azima Tetracantha Leaves Extract Lipid Pro Ile Marsupporting
confidence: 91%